To integrate or not to integrate? Understanding B2B social media communications. Issue 1 (12th February 2018) - Gruner, Richard L.; Power, Damien
Abstract : Purpose: Social media communications on platforms such as Facebook and LinkedIn can allow managers to interact cost effectively with trading partners. However, although most firms have an online presence on multiple social media platforms, the question remains as to whether marketers' widespread social media investments are beneficial for firms. The paper aims to discuss this issue. Design/methodology/approach: This paper presents competing hypotheses to explore how firms' investment in one form of social media impacts activity on another form of social media. To do so, the authors draw on a data set of 208 large Australian organizations using objective social media activity metrics that measure business-to-business (B2B) audience engagement. Findings: The findings suggest that widespread social media activity on LinkedIn, Twitter, and YouTube negatively affects a firm's marketing activity on Facebook. The results indicate that having a social media preference whereby firms focus on a specific social media platform is more effective in forming successful inter-organizational relationships than a multiplatform approach. Originality/value: The study contributes to the sparse research that seeks to leverage social media for audience engagement beyond a business-to-consumer context. The study's findings provide insights into the key mechanisms that underlie firms' B2B social media strategies, and in so doing, offer a fresh perspective on the importance of interactive marketing communication.